Implementación De Un Sistema De Encuestas Para Los Procesos Sustantivos De La Universidad Nacional De Chimborazo Utilizando Lambdas En El Framework.Net.6.0 - García Jaramillo, Gandhy Armando (2024)
The National University of Chimborazo faced the need to establish a survey system to evaluate its fundamental processes, aiming to elevate the instructional standard offered to students and improve the effectiveness of administrative procedures. Currently lacking an effective tool for conducting these surveys efficiently, the creation of a survey system based on .Net 6.0 technology framework was proposed, utilizing lambdas to enhance system efficiency and scalability. This solution enabled the university to create, manage, and analyze surveys efficiently, ensuring the quality and accuracy of the collected data. Additionally, this system facilitated the creation of customized surveys for various audiences, including students, professors, and administrative staff, along with data analysis tools to obtain valuable insights supporting decision-making and enhancing educational quality. In summary, implementing an efficient and scalable survey system based on .Net 6.0 technology framework and lambdas would be crucial for enhancing the efficiency of the university's substantive processes. Incorporating performance evaluation with SolarWinds Web Performance Monitor demonstrated a practical concern for efficiency and user experience within the survey system context. This approach strengthened the research and reflected the commitment to building a robust and effective system for the National University of Chimborazo